Development of a fatigue model useful in ship routing design - Mao, Wengang; Ringsberg, Jonas; Rychlik, Igor; Storhaug, Gaute (2011)
In this paper, a simple fatigue estimation model using only encountered significant wave height, is used for predicting fatigue accumulation of a vessel during a voyage. The formulation of the model is developed based on the narrow-band approximation. It is assumed that the significant response range, hs, has a linear relationship with encountered significant wave height, Hs. The mean stress up-crossing frequency, fz, is represented by the corresponding encountered wave frequency and it is expressed as a function of Hs. The capacity and accuracy of the model is illustrated by application to one container vessel’s fatigue damage accumulation in an amidships detail, operating in the North Atlantic during 2008. For this vessel, all the necessary data needed in the fatigue model, and for verification of it, was obtained by measurements. The results from the proposed fatigue model are compared with the well-known and accurate rainflow analysis. Influence of nonlinearities, e.g. whipping, on fatigue damage predictions and extreme responses is also discussed.